Práticas de preservação do acervo de obras raras do Centro de Memória da Amazônia (CMA): o caso Severa Romana - CASTRO, Ruan Denner Gomes de (2021)
Preservation strategies analysis on Severa Romana criminal process, a young woman murdered in the early twentieth century and raised to the status of "saint" in Belem’s reality, located in the of the Amazon Memory Center (AMC) rare works collection. The research is based on a bibliographical survey and case study, using questionnaires and interviews as a way to collect data for AMC’s employees. The research was conducted aiming to analyze the preservation and conservation potential techniques applied in these documentary items to access, diffuse and revitalize the memory of Severa Romana. The research identified that, although localized preservation strategies, especially related to hygiene, were identified, the potential of access and diffusion is only glimpsed, due to access restrictions offered to the process, considering different ways of revealing this documentation from digital formats.